Implementation of Islamic-based curriculum in cultivating religious character at Al-Ikram Islamic School Medan - Hotmasarih Harahap; Ali Imran Sinaga; Solihah Titin Sumanti (Himpunan Pengembang Kurikulum Indonesia, 2024)
Character education is an educational effort that aims to improve the quality of educational processes and outcomes that lead to the formation of students' character and noble morals as a whole, integrated and balanced following graduation competency standards in each educational unit. Based on the decree of the Minister of Education and Culture of the Republic of Indonesia Number 719/P/2020 concerning Guidelines for implementing curriculum in educational units in special conditions, it provides flexibility for schools to choose a curriculum that suits students' learning needs. In this way, Al-Ikram Islamic School Medan, apart from using the independent curriculum as the national curriculum, also uses the Islamic-based curriculum as a companion curriculum according to the needs of students. This research was conducted to analyze the background of the Islamic Based Curriculum at Al-Ikram Islamic School Medan; To analyze the role of the Islamic Based Curriculum in cultivating religious character at Al-Ikram Islamic School Medan; To analyze the implementation of the Islamic Based Curriculum at Al-Ikram Islamic School Medan; To analyze the evaluation of the Islamic Based Curriculum at Al-Ikram Islamic School Medan. The research method used in this research is a qualitative method with a descriptive/analytic type. The results of this research show that the implementation of the Islamic Curriculum at Al-Ikram Islamic School Medan is effective in instilling religious character, developing academic potential, and forming students with noble character and strong faith. Abstrak Pendidikan karakter adalah upaya pendidikan yang bertujuan untuk meningkatkan mutu proses dan hasil pendidikan yang mengarah pada pembentukan karakter dan akhlak mulia peserta didik secara utuh, terpadu dan seimbang sesuai dengan standar kompetensi kelulusan pada setiap satuan pendidikan. Berdasarkan keputusan menteri Pendidikan dan kebudayaan Republik Indonesia Nomor 719/P/2020 tentang Pedoman pelaksanaan kurikulum pada satuan pendidikan dalam kondisi khusus memberikan fleksibilitas bagi sekolah untuk memilih kurikulum yang sesuai dengan kebutuhan pembelajaran peserta didik. Dengan begitu Al-Ikram Islamic School Medan di samping menggunakan kurikulum merdeka sebagai kurikulum nasional juga menggunakan Islamic Based Curriculum sebagai kurikulum pendamping sesuai dengan kebutuhan peserta didik. Penelitian ini dilakukan dengan tujuan unuk menganalisis latar belakang Islamic Based Curriculum di Al-Ikram Islamic School Medan; Untuk menganalisis peranan Islamic Based Curriculum dalam penanaman karakter religius di Al-Ikram Islamic School Medan; Untuk menganalisis penerapan Islamic Based Curriculum di Al-Ikram Islamic School Medan; Untuk menganalisis evaluasi Islamic Based Curriculum di Al-Ikram Islamic School Medan. Metode penelitian yang digunakan dalam penelitian ini adalah metode kualitatif dengan jenis deskriptif/analitik. Hasil penelitian ini adalah penerapan Islamic Based Curriculum di Al-Ikram Islamic School Medan efektif dalam menanamkan karakter religius, mengembangkan potensi akademik dan membentuk peserta didik yang berakhlak mulia dan beriman kuat. Kata Kunci: karakter; kurikulum berbasis Islam; religius